Effects of meso‐ and microhabitat characteristics on the coexistence of two native gammarid species (Crustacea, Gammaridae). Issue 1 (May 2017) - Mauchart, Péter; Czirok, Attila; Horvai, Valér; Herczeg, Róbert; Móra, Arnold; Csabai, Zoltán
Abstract : Although the influence of invasive species on the distribution of native species is well‐studied, our knowledge on the processes driving the co‐occurrence of native gammarid species is limited. We studied the co‐occurrence of two common European gammarids, Gammarus fossarum and Gammarus roeselii, along a stream continuum in Mecsek Mountains, SW Hungary. We hypothesized that (1) the large scale distribution is influenced by microhabitat diversity; (2) the distribution of each species is equal among the available microhabitats in the absence of a competitor; (3) microhabitat preference is evident in the case of coexistence; and (4) the mesohabitat structure influences the microhabitat preference. A longitudinal gradient was observed along the stream: The dominance of G. fossarum at upstream sections continuously transitioned into the dominance of G. roeselii through an intermediate section, where both species coexisted. This distribution cannot be completely explained by the microhabitat diversity. In cases of single species occurrences, no microhabitat preference was found in G. fossarum, whereas G. roeselii preferred lithal and biotic microhabitats. The presence of a competitor significantly modified the microdistribution: G. roeselii retreated from lithal microhabitats and G. fossarum almost disappeared from gravel. Moreover, the location of microhabitats within mesohabitats significantly affected the distribution of gammarids. Both species occurred in meso‐ and microhabitat combination resembling their habitat usually occupied along the stream continuum: G. fossarum was an indicator species for the fast‐flowing shallow riffles with the dominance of lithal microhabitat, whereas G. roeselii was abundant in the slow‐flowing deeper pools usually characterized by vegetation or organic matter. Our results suggest that, beyond the large scale longitudinal distributional pattern and species‐specific life‐cycles, the meso‐ and microhabitat characteristics of a stream can drive stable and long‐term coexistence among G. fossarum and G. roeselii .